The Guest-Spectator - Piergiorgio Giacché (Università degli studi di Perugia – Perúgia, Itália) (Revista Brasileira de Estudos da Presença, 2013)
This text discusses the reflections of an anthropologist who followed for many years the performative activities of Thomas Richards, which are a continuation of Jerzy Grotowski’s research on art as a vehicle. We do not enter into the specifics of techniques and work methods, but we do discuss the effects, or rather the reflexes of a series of works which are not conceived of as spectacles to be seen by a public, but as progressive and partial outcomes of work based on the indissoluble union between action and vision in the performer’s body and in the field of the autonomous scene. What do spectators see and feel, and how can they feel involved? What form of contact or contagion can be seen in a scene that does not seem like a spectacle? And in the course of successive rehearsals of this art as a vehicle, how and when occurred a change in the role and way of being of the guest-spectator of an inner action, which does not open up to those who watch, but is consummated in the verticality of the Performer’s actions and singing?